Policy Elements Influencing the Sustainability of the Biosimilar Market in Malaysia: A Review - Hoang Nguyen Thao My; Muhammad Junaid Farrukh; Fazlollah Keshavarzi, (Malaysian Journal of Science (MJS), 2025)
Sustaining the market for biosimilars is key to securing the long-term benefits from biosimilar medicines. Policy can influence the achievement of those elements that contribute to the sustainability of biosimilars. Despite being the first country to implement regulatory guidelines for the approval and marketing of biosimilars, the availability and adoption of biosimilars in Malaysia remain suboptimal. This study aims to create the roadmap of policy elements that influence the sustainability of the biosimilar market in Malaysia. The study searched and reviewed articles in PubMed, Google Scholar, National Library of Medicine from 1/1/2003 to 14/04/2024. A total of 3469 results were found, with PubMed contributing 39 records (n=39), Google Scholar contributing 3074 records (n=3074), and the National Library of Medicine contributing 356 records (n=356). The biosimilars policy framework and sustainability measures were adopted from IQVIA Country Scorecards for Biosimilar Sustainability. After eliminating duplicates and applying selection criteria, 20 articles were chosen for review. The selection was justified based on relevance to the five policy domains: regulatory environment and clinical guidelines, awareness and education, incentives, pricing rules and dynamics, and purchasing mechanisms. The 20 selected papers were categorized into five main domains: regulatory environment and clinical guidelines, awareness and education, incentives, pricing rules and dynamics, and purchasing mechanisms. The analysis revealed positive developments in regulatory compliance and clinical guidelines, pricing regulations, and purchasing mechanisms. However, challenges were identified in the areas of awareness and education, pricing rules and dynamics, and incentives. Awareness and education challenges were primarily attributed to limited pharmacist training and physician skepticism regarding biosimilars. Additionally, the absence of strong financial incentives and limited patient education hindered adoption. The "single-winner tendering system" constrained market diversity, restricting competitive pricing. The literature review emphasizes the need for setting up specific prescription targets, promoting competition, and offering incentives to biosimilar manufacturers to increase market appeal. Furthermore, it is critical to enforce strict quality standards for the incorporation of tenders and align the registration requirements with global standards. Education for pharmacists and continuous training for healthcare practitioners are also essential. In Malaysia, these steps are crucial in ensuring the affordability and accessibility of biosimilars. Improving these policy components could help Malaysia create a competitive biosimilar market, increase access to affordable treatments, and eventually raise the standard of healthcare service.